‘Uluww al-Isnad dalam Periwayatan Hadis Abu Muhammad al-Husain bin Mas‘ud al-Baghawi - Romlah Abubakar Askar; Abdurrahim Yapono (Universitas Darussalam Gontor, 2016)
Abu Muhammad al-Husayn Ibnu Mas’ud al-Baghawi (450-516H) was one of the leading scholars in Tafsir (Quran exegesis), hadith (prophetic tradition), and fiqh (Islamic legal jurisprudence) in his era. He was categorized as muta’akhirūn (scholars who came later on) and was instrumental in the development of these three disciplines. In the field of exegesis, he was among the scholars who used al-Ma’tsūr, (commentary stylist), relying on the verses of the Qur’an, hadith, and the statements from the followers of the tabi’īn (the followers of the followers). This can be found in his recorded work Ma’ālim al Tanzīl. In the field of hadith, he preserved the narration method and presenting a new approach by merging some patterns of hadith narration from several books of hadith in his work known as ṭarīqah al-Jam’u (combination [amalgamation] method). This pattern will not occur unless there is the existence of other transmission lines as a second chain of narration used to produce ‘uluww al-Isnād (the noble sanad) or nuzūl al-Isnād (descent sanad). It is recorded in his works: al-Jam’u baina al-Ṣaḥīḥain, Sharḥ al-Sunnah and Maṣābiḥ al-Sunnah. In the field of Jurisprudence, he was amongst those mujtahidin from the Shafiee school of thought, recorded in his Majmū’ ‘al-Fatāwā, al-Kifāyah fī al-Furū’ and Kitāb al-Tahdzīb. This paper aims to examine one of al-Baghawi’s skills in sanad collection which is the uluww al-isnād and nuzūl al-isnād, recorded from his two works Ma’ālim al-Tanzīl and Syarḥ al-Sunnah. The quantitative, qualitative and comparative approach has been used in this study to give an authentic description of the terms ‘uluww al-isnād, nuzūl al-isnād from al-Baghawi. Studies have found there are many examples of uluww al-Isnād and nuzūl al-isnāds contained in the patterns of al-Baghawi’s chain of narration towards the Ṣaḥīḥayn of al-Bukhari and Muslim as the mustakhrij (the validator of both).